"No reason for children to go hungry": Rural U.S. caregivers' perceptions of elected officials and their impacts on food policy. - Annie Hardison-Moody; Lindsey Haynes-Maslow; Sarah K Bowen (PLoS ONE)
In the context of the increasingly polarized U.S. political environments of the 2016 and 2020 elections, how did rural caregivers think about food and health policies? To answer this question, researchers interviewed 50 low-income women living in two rural N.C. counties in 2016/7 and 2020 as part of a broader longitudinal qualitative study of family food environments. As participants reflected on elections and food assistance policies, caregivers focused on their experiences as mothers and described current or potential policies and programs in light of how they would impact their children. Caregivers also made recommendations for universal and inclusive policies that would improve their access to food. However, their responses were also racialized, with White caregivers more likely to use tropes of "deservingness" when discussing public benefits. To improve food security in rural areas, researchers should center rural low-income women's perspectives when developing food policy, particularly given the important role mothers play in feeding their families and mitigating the impacts of food insecurity.